Overcoming Barriers in the Management of Hypertension: The Experience of the Cardiovascular Health Program in Chilean Primary Health Care Centers - Daniela Sandoval; Miguel Bravo; Elard Koch; Sebastián Gatica; Ivonne Ahlers; Oscar Henríquez; Tomás Romero (International Journal of Hypertension)
Objective. To assess the blood pressure control and cardiovascular risk factors (CVRFs) in a population of hypertensive patients with access to care under a government-financed program, the Cardiovascular Health Program (CHP). Design. A cross-sectional and multicenter study. Setting. 52 primary care centers, metropolitan area of Santiago, Chile. Participants. 1,194 patients were selected by a systematic random sampling from a universe of 316,654 hypertensive patients. Key Measurements. Demographic information, blood pressure (BP) measurements, and CVRF were extracted from medical records of patients followed for a 12-month period. Results. 59.7% of patients reached target BP <140/90 mmHg. More women were captured in the sampling (2.1 : 1), achieving better BP control than men. Diabetic patients (26.4%) had worse BP control than nondiabetics. Antihypertensive medications were used in 91.5%, with multidrug therapy more frequent in patients with higher BP and more difficult control. Conclusions. The success in improving the BP control to values <140/90 mmHg from 45.3% to 59.7% underscores the contribution of this program in the Chilean primary care cardiovascular preventive strategies. However, fewer hypertensive men than women were captured by this program, and it is of concern the underperforming of BP control observed in diabetics.